FEATURES OF RELATIVE AIR HUMIDITY REGIME IN A LARGE CITY (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
An analysis of the average annual and monthly characteristics of the relative air humidity (RAH) regime in the Minsk City showed that in 1980–2022. In the City, RAH is characterized by small interannual and significant seasonal variability, as well as a tendency to a slight increase in its annual values. The average annual RAH was 77․3% with a Cv of 2․20%. The number of days with RAH ≥80% is characterized by moderate temporal variability and a tendency to decrease their number. The average annual number of days with RAH ≥ 80% was 176 days, with a Cv of 9․69%. An analysis of the seasonal dynamics of RAH in Minsk showed that its highest values were observed in winter and amounted to 86․0%, with a Cv of 1․73%. In spring, RAH was the lowest of all seasons of the year – 69․6%, with a Cv of 4․14%.
Keywords: relative air humidity; city; climate; forecast scenario